ANALISIS PEMBANGUNAN PADA KAWASAN BEKAS PERTAMBANGAN BAUKSIT DI DESA MAROK KECIL, KECAMATAN SINGKEP SELATAN, KABUPATEN LINGGA - Siti Maryani; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Mining activities in most of Indonesia’s regions rarely pay attention to sustainable development, which is mining activities do not pay attention to the economic, social and environmental sustainability of the mining area. In the Marok Kecil village there was once a bauxite mining activity which at the moment is not longer operating. The purpose of this research is to analyze how development on ex-bauxite mining area in the Marok Kecil village and what are the factors influencing development on ex-bauxite mining area in the Marok Kecil village.This research was conducted at Marok Kecil village, South Singkep Sub Districs, Lingga Regency. The theory used in this research is Asdak’ theory, there are have three concepts of sustainable development that is sustainability of social system, sustainability of economic and ecological sustainability. The researh method used is descriptive qualitative research with data collection technique done through interview, observation and documentation. Selection of research informant using purposive sampling technique for Ltd Sanmas Mekar Abadi and accidental sampling techique for people in Marok Kecil Village.The result of this research indicate that the presence of influencing factors of development on ex-bauxite mining activities in the Marok Kecil village . That factors is not tranparancy regarding the use of funds for development, the existence of interest factors of certain people in the realization of development, lack of community knowledge about the use of ex-mining land and lack of community participation in developmnet-related activities.Keywords: Sustainable Development, Bauxite Mining.